A Research Framework for the Clean-Slate Design of Next-Generation Optical Access - Joseph Kim (Fiber and Integrated Optics, 2012)
A comprehensive research framework for a comparative analysis of candidate network architectures and protocols in the clean-slate design of next-generation optical access is proposed. The proposed research framework consists of a comparative analysis framework based on multivariate non-inferiority testing and a notion of equivalent circuit rate taking into account user-perceived performances and a virtualtest bed providing a complete experimental platform for the comparative analysis. The capability of the research framework is demonstrated through numerical results from the study of the elasticity of hybrid time division multiplexing/wavelength division multiplexing–passive optical network based on tunable transceivers.